Perlindungan Konsumen Pembelian Rumah Indent Siap Huni Terhadap Perilaku Ingkar Janji Developer Dalam Putusan Nomor 64/Pid.Sus/2023/PN Smg - Nabila Khairunnisa Azizia (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Home is one of the needs that humans must have. This increasing need has led to developments in the housing sector. Developers or developers with all marketing strategies to attract potential consumers, Decision Number 64/Pid.Sus/2023/PN. SMG as a basis for researching consumer rights that have been violated and efforts to restore consumer rights. The writing method in this research uses a normative juridical method using secondary data, namely primary, secondary and tertiary legal materials carried out by literature study. The legal relationship between the two parties is a sale and purchase agreement. The agreement between consumers and business actors complies with Article 1320 of the Civil Code, and rights and obligations arise for the parties. Business actors promised to complete the development but were not fulfilled. Business actors violate the obligation to have good faith in carrying out their business, and offer goods that do not comply with the agreement. By not fulfilling these obligations, consumers' rights are violated because business actors do not provide correct, clear and honest information regarding the condition of the goods. Consumers can file claims for breach of contract against business actors. Business actors guarantee SHM to other parties without permission, causing losses to consumers, so compensation can be requested, according to the elements of an Unlawful Act, as well as imposing mortgage rights on the parties to declare the mortgage rights null and void. In this way, preventive and repressive protection can be created to provide protection for the parties.